2020
DOI: 10.1177/1369433220921000
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of grey wolf optimization algorithm for damage detection of skeletal structures via expanded mode shapes

Abstract: Vibration-based structural damage identification through optimization techniques has become an interesting research topic in recent years. Dynamic characteristics such as frequencies and mode shapes are used to construct the objective function. The objective functions based on only frequencies are not very sensitive to damage in large structures. However, objective functions based on both mode shapes and frequencies are very effective. In real measurement condition, the number of installed sensors is limited, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
32
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 75 publications
(32 citation statements)
references
References 46 publications
0
32
0
Order By: Relevance
“…In their research, they investigated numerical and experimental examples of large-scale space truss and four-story steel frame, respectively. [42] SSA-based method has recently showed very promising results for FEM updating and damage detection in different damage cases of small-and large-scale shear buildings. Ghannadi and Kourehli have employed SSA to minimize an objective function based on natural frequency differences and NFVAC.…”
Section: Introductionmentioning
confidence: 99%
“…In their research, they investigated numerical and experimental examples of large-scale space truss and four-story steel frame, respectively. [42] SSA-based method has recently showed very promising results for FEM updating and damage detection in different damage cases of small-and large-scale shear buildings. Ghannadi and Kourehli have employed SSA to minimize an objective function based on natural frequency differences and NFVAC.…”
Section: Introductionmentioning
confidence: 99%
“…As an important structural member, beams have been studied for several decades. A large number of fundamental studies on beam analysis have been reported in the literature including in classical literature, and for practical applications such as the analysis of steel structures, concrete structures 30–32 nanomaterials, 3239 and functionally graded materials, 40 to cite a few examples. In all these applications, an in-depth understanding of the mechanics of beam analysis plays an important role.…”
Section: Introductionmentioning
confidence: 99%
“…Au et al (2003) presented an application of SEREP expansion and genetic algorithm for damage assessment in beam-like structures. Ghannadi et al (2020) proposed a methodology of damage detection based on SEREP expansion and grey wolf optimizer. Abdollahi and Tavakkoli (2019) employed two mode shape expansion techniques namely SEREP, and dynamic expansion to estimate the unmeasured modal data in solid structures.…”
Section: Introductionmentioning
confidence: 99%